Penerapan Metode Role Playing dalam Meningkatkan Keterampilan Berbicara Anak dan Kecerdasan Sosialnya - Moh. Hilmi (LP2M STIT Palapa Nusantara, 2018)
This research is based on the problem of the still low social and speaking skills of children, and in general the problem of this research is